First European quality of life survey quality of life in Bulgaria and Romania - Marginean, Ioan.; Precupetu, Iuliana; Tzanov, Vassil; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2006)
Following enlargement in May 2004, the European Union is increasingly being characterised by a variety of economic, social and cultural differences among its Member States. Thus, an important focus of EU social and economic policy is to foster economic and social cohesion in order to reduce the inequalities that are currently visible across Europe, lowering the gap between older and new Member States with respect to living and working conditions. Further enlargement of the EU through the accession of Bulgaria and Romania, which is scheduled for 2007, will bring to the fore once again the issue of economic and social inequalities and the need for policies aimed at moderating differences, while still maintaining a positive overall trend of growth.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- Bulgaria -- Research; Quality of life -- Romania -- Research; Electronic books